Erectile dysfunction in testicular cancer patients treated with chemotherapy - Tasdemir, C.; Firdolas, F.; Harputluoglu, H.; Altintas, R.; Gunes, A. (Wiley, 2012)
Information on male potency in testicular cancer (TC) patients treated with chemotherapy is insufficient. We aimed to assess the levels of depression and anxiety symptoms, sexual function and gonodotrophins. Participants (n similar to=similar to 27) were identified and recruited from the genitourinary services of two medical centres, one in Inonu University and the other in the Firat University. All patients are TC patients treated with chemotherapy after unilateral orchiectomy. Participants completed follow-up assessments after the completion of the chemotherapy regimen. Serum luteinising hormone, follicle-stimulating hormone and testosterone levels were determined after blood samples had been taken in the morning after an overnight fast. International Index of Erectile Function (IIEF-15) was also used to evaluate erectile dysfunction (ED) score. Beck Depression and Beck Anxiety Scale were used to assess psychological symptoms. The findings indicated that men treated with chemotherapy had significantly different IIEF-15 and Beck Anxiety scores compared with men who did not receive chemotherapy. But no statistically significant difference was determined in the serum gonodotrophin levels and depression score between the two groups. It is concluded that patients with TC undergoing chemotherapy have greater risk than normal men for ED, independently of the gonodotrophin's level.
Keywords: Chemotherapy; erectile dysfunction; testicular cancer